Igrifikacija v storitvenem marketingu - Černič, Nina (Akademija MM, 2018)
This paper explores gamification as a concept that is increasingly gaining ground in the marketing literature and practice. It deals with the question of the importance of the game elements in non-gaming contexts and explores the importance of these elements for marketing practice. In the empirical part the paper focuses on the impact of the elements of games on dimensions of customer experience when buying airline tickets, relying on the PENS model (Player Experience of Need Satisfaction), which measures the dimensions of the user experience of players of video games. The results of the exploratory study conducted as a quasi-experiment show that the elements that increase emotional involvement and physical presence have a statistically significant positive impact on the user experience. The paper further discusses the research findings and their potential contribution to research and practice.
Keywords: marketing; teorija iger; trženje